The Impact of the Professional Competence of the Internal Auditor in Improving the Quality of Accounting: Analytical Study - Kadim, Jasim Rahi; Sabti, Yousif Mousa; Ali, Ghazanfar; Khdair, Wameedh A.; Shaltag, Karim Hazen (South Asian Journal of Social Sciences and Humanities, 2021)
The aim of the research is to test the impact of the professional competence of the internal auditor in improving the quality of accounting information (QAI). The research community consists of a group of Iraqi private banks listed in the Iraqi Stock Exchange, and the research sample includes accountants, internal auditors and internal audit managers, and for the purpose of data collection, the researcher prepared a questionnaire form, as (52) forms were distributed to the individuals of the research sample and (49) forms were recovered from them, and the form valid for analysis reached (44) forms. The data of which were analyzed using the statistical package (SPSS). The research reached conclusions, including the existence of a correlation and moral effect between the variables of the research, and among the recommendations made by the research directing banks’ attention to the need to continue holding conferences and seminars in coordination with the competent bodies and academics to develop the capabilities and capabilities of internal auditors in companies.
Keywords: Professional competence; Quality of accounting information; Iraqi commercial; banks